Gas Chromatographic Analysis of Triglycerides - The Reference Method for Testing Purity of Milk Fat and Perspectives on its Use in India: A Review: GC analysis of triglycerides for testing purity of milk fat - Aparnathi , K D; Patel, Ajit; Mehta, Bhavbhuti M.; Patel, Deep; Prajapati, J B (Indian Journal of Dairy Science, 2023)
Adulteration of milk fat is burning issue, as traditional parameters for testing its purity are becoming ineffective due to advances in practices employed for the adulteration. Gas chromatographic (GC) analysis of intact triglycerides appears as the most promising method for combating menace of the high tech adulteration of milk fat, since it is simple, rapid, robust and comprehensive. Unfortunately, use of this method in India may cause problem of false positive results due to its specifications of parameters suggested on purity of milk fat. Hence, for adopting the method in India, modifications are required in limits of specifications on some parameters. The modifications in specifications of the method require extensive survey to generate database on the parameters. Outcome these efforts will be helpful to recognise Indian milk fat as pure in international market, whenever tested by this method. Until the method gets official endorsement, Indian dairy industry may avail its unmatched advantages by using it as a screening tool. Since, no comprehensive publication on this method is available so far in the literature, an attempt is made in this paper to collate information on its genesis, development, adoption as reference/standard, basic principle, operational steps, advantage, limitations and evaluation. This review paper serves a navigation tool for concerned scientists and users of the method to understand its fundamentals aspects, identify reasons for false positive results occur in its use and develop appropriate solutions to resolve the problems as well as improve its application.